A Japanese diet with low glycaemic index and glycaemic load is associated with both favourable and unfavourable aspects of dietary intake patterns in three generations of women. Issue 4 (7th November 2016) - Inomaki, Ryoko; Murakami, Kentaro; Livingstone, M Barbara E; Okubo, Hitomi; Kobayashi, Satomi; Suga, Hitomi; Sasaki, Satoshi
Abstract: Objective: Western studies have suggested cultural differences in food and nutrient intake patterns associated with dietary glycaemic index (GI) and glycaemic load (GL). Here, we conducted a cross-sectional study to examine the GI and GL of Japanese diets in relation to food and nutrient intakes. Design: Dietary intake was assessed using a validated, self-administered, diet history questionnaire. Setting: A total of thirty-five of forty-seven prefectures in Japan. Subjects: Young (age 18 years), middle-aged (mean age 48 years) and older (mean age 74 years) Japanese women ( n 3961, 3800 and 2202, respectively). Results: Irrespective of age, a positive association with dietary GI was seen for white rice only, which contributed most (37–42 %) to the variation in dietary GI. Conversely, all other food groups (such as fruit and vegetable juice, dairy products, noodles and fruit) were negative predictors of dietary GI. For dietary GL, 95–96 % of variation was explained by carbohydrate-rich food groups, all of which were positive predictors of GL. After adjustment for potential confounding factors, only carbohydrate intake was positively associated with dietary GI and GL, irrespective of age. Conversely, dietary GI and GL were inversely associated with intakes of all other nutrients examined (including SFA and Na). Conclusions: A low-GI and -GL diet, which was characterized principally by a low intake of white rice, was associated with both favourable (higher intakes of dietary fibre and key vitamins and minerals) and unfavourable (higher intakes of SFA and Na) aspects of dietary intake patterns in three generations of Japanese women.